Macroeconomic drivers and the pricing of uncertainty, inflation, and bonds - Brandyn Bok; Thomas Mertens; John C. Williams (Federal Reserve Bank of New York, 2022)
This paper analyzes a new stylized fact: The correlation between uncertainty shocks and changes in inflation expectations has declined and turned negative over the past quarter century. It rationalizes this fact within a standard New Keynesian model with a lower bound on interest rates combined with a decline in the natural rate of interest. With a lower natural rate, the likelihood of the lower bound binding increased and the effects of uncertainty on the economy became more pronounced. In such an environment, increases in uncertainty raise the possibility that the central bank will be unable to eliminate inflation shortfalls following negative demand shocks. As a result, the observed decline in the correlation between uncertainty and inflation expectations emerges. Average-inflation targeting policies can mitigate the longer-run effects of increases in uncertainty on the real economy.
Keywords: E52; 330